MicroRNA-505 suppresses gastric cancer cell proliferation and invasion by directly targeting Polo-like kinase-1 - Dang, Sheng-Chun (Onco Targets Ther, 2019)
PURPOSE: The expression of microRNA-505 (miR-505) has been investigated in various cancers; however, its effect and mechanism in relation to gastric cancer (GC) are yet to be determined. Thus, the current evaluation aimed to examine the expression and potential role of miR-505 in GC. MATERIALS AND METHODS: Quantitative real-time PCR was carried out to analyze miR-505 expression in GC cells and tissues. We observed that miR-505 is differentially expressed in GC cells following transfection of its mimics or inhibitors. Changes in cell invasion, cell proliferation, and epithelial–mesenchymal transition markers were measured. RESULTS: These findings indicated that miR-505 expression is downregulated in both GC cell lines and GC tissues. In addition, knockdown miR-505 induced the invasion and proliferation of GC cells. Transfection of miR-505 mimics led to an elevation in N-cadherin expression but a decrease in E-cadherin expression. Furthermore, we have shown that miR-505 binds to the 3′-UTR region of Polo-like kinase-1. CONCLUSION: Our results indicated that miR-505 suppresses GC cell proliferation and invasion; it may be a valuable candidate gene for seeking therapy strategy for GC.